Methane accumulation and release from deep peat: Measurements, conceptual models, and biogeochemical significance - Glaser, Paul H.; Chanton, Jeffrey P. (Carbon Cycling in Northern Peatlands, 2009)
Northern peatlands account for more than half the world's wetlands but are currently estimated to contribute only about a third of the total methane emissions from all wetlands. Increasing data on the dynamics of methane gas bubbles in peat deposits now suggest that these estimates may need to be scaled upward. Rates of methanogenesis may remain high in deep peat strata because of the downward transport of labile root exudates permitting the widespread production of gas bubbles. Recent investigations using an array of methods have reported free-phase gas volumes of 10–20% within both deep and shallow peat strata and episodic ebullition fluxes exceeding 35 g CH4 m−2 per event. Gas bubbles accumulate in overpressured pockets that episodically rupture in response to steep declines in atmospheric pressure or declining water tables. Although these ebullition fluxes are highly variable in both time and space, they appear to dominate the annual methane emissions from northern peatlands and represent a major and underappreciated element of the global methane cycle.
id: 1972
Keywords: Carbon cycle (Biogeochemistry)—Northern Hemisphere; Carbon sequestration—Northern Hemisphere; Greenhouse gases—Northern Hemisphere; Peatlands—Environmental aspects—Northern Hemisphere